ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP PADA MATERI FUNGSI KUADRAT - Jenny Shara; Gida Kadarisma; Wahyu Setiawan (Journal on Education, 2019)
This study aims to describe the mathematical critical thinking skills of class IX junior high school students in Maleber and examine errors in solving test questions regarding material quadratic functions. The research method used is the description method. The study was conducted with the subjects of the research were 34 IX grade junior high school students in Maleber. The test questions given are in the form of 3 questions. Data were analyzed based on FRISCO critical thinking indicators where there were several stages used, namely data reduction, data presentation, and conclusion drawing. The results of the study show that the profile of critical thinking students is high, medium, and low mathematical abilities in solving problems in the problem. At the stage of understanding the problem, high and moderate ability students can express what is known and asked in the questions in detail. While students with moderate and low ability have difficulty in finding alternative solutions.